Properties of foamed concrete containing water repellents. (1st October 2016) - Ma, Cong; Chen, Bing
Highlights: A foamed concrete modified by water repellent with low water absorption is prepared. The effects of water repellent on the physical and mechanical properties are investigated. The hygroscopic fitted curves from KUM and CUB models are established. Abstract: It is generally known that the physical and mechanical properties would be greatly degraded after water or moisture transferring into the foamed concrete. In this study, a foamed concrete with a low density of about 550 kg/m 3 is prepared using ordinary Portland cement, and three types of water repellents including potassium trimethylsilanolate (PT), calcium stearate (CS) and siloxane-based polymer (SP) are employed to decrease the water absorption of the foamed concrete. The effects of the water repellent on the mechanical and physical properties of the foamed concrete, such as 7-day and 28-day compressive strength, thermal conductivity, sorptivity and hygroscopicity, are studied. The laboratory results indicate that the water repellents improve the compressive strength to some extent without sacrificing the thermal insulation property of the foamed concrete. The sorptivity evaluated by 48-h water absorption and strength retention coefficient ( RS ) is significantly improved as increasing the content of water repellent. When 1.0% SP is used, the water absorption and RS value of the foamed concrete with 28-day strength of 1.77 MPa and thermal conductivity of 0.150 W/m K are 2.5% (by volume) and 0.989, respectively. In addition, the contents of hygroscopic moisture [ W ( φ )] also decrease with the increasing content of water repellent. The hygroscopic fitted curves with high coefficients of determination obtained the KUM and CUB models have been proved applicable in exploring the relationship of the W ( φ ) to the relative humidity.